Effect of water vapor pressure on fatigue crack growth in Al–Zn–Cu–Mg over wide-range stress intensity factor loading. (March 2015) - Burns, J.T.; Bush, R.W.; Ai, J.H.; Jones, J.L.; Lee, Y.; Gangloff, R.P.
Abstract: Investigation of the deleterious effect of high purity water vapor on fatigue crack growth rate (d a /d N ) in 7075-T651 shows that growth rate declines with decreasing water vapor pressure ( P H2O ) over a wide range of stress intensity range (Δ K ). Decreasing Δ K experiments exhibit a novel minimum in d a /d N for intermediate P H2O and low Δ K . This minimum and testing protocol dependent environmental-fatigue behavior are explained by crack wake fracture morphology and R -dependent crack opening displacement effects on molecular flow to the crack tip. This environmentally-based mechanism leads to the onset and reversal of a non-conservative and false high threshold stress intensity range.